Sociodemographic characteristics of the patients of Tonsillitis attended in OPD of a district level Hospital (Bangladesh Journal of Otorhinolaryngology, 2020)
Aim: To find out the tonsillitis patients and also find out its sociodemographic characteristics in district level of Bangladesh.Method: This was a prospective cross sectional study, which was carried in out patients of tonsillitis attended in OPD of 250 Bedded General Hospital, Gopalganj. All the patients of acute tonsillitis, chronic tonsillitis and adenoid hypertrophy were selected from OPD irrespective of sex during the period of July 2015 to June 2016. Age ranges from 0-90 years and person residents of Gopalganj and adjacent districts.Result: In this study 45.54% were male and 54.46% were female. Male female ratio 1:1.2.Majority of patients were age group 0-15 years (55.97%) Mean age of patient 45 years. Maximum family had monthly income TK 10,000 to 20,000 and maximum patients were dependent (30%) 5-6 family members were highest group, 60% patients lived in katcha house, 75% lived in rural area 35% patients used to bath in pond and majority of patients primary and JSC qualification. The majority of signs and symptoms were sore throat (100%), red, swollen tonsil (26%); white pus filled spots on the tonsil (38%); swollen lymph node in neck (60%) and bad breath (halitosis) (38%).Conclusion: Tonsillitis is still high in rural area of our country and commonly found in younger age group. Thus improvement of related socioeconomic factors, health awareness campaign, improved health education and early accessibility can reduce the incidence of disease.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 180-186